Programy typu reality show – perspektywa edukacyjna - Przybyła, Tomasz (Wydawnictwo Naukowe UAM Poznań, 2008)
We all live in the world that is being created by media reality and the typical spectator more and more often identifies the mass media transmission with the truth. Media evolves around us all creating the new shows all the time. This is how the reality show was created – the ‘mega’ kind of all the shows. Although not real, those programmes for lots of us are so close that they become a part of our ordinary lives. We, as the viewers assume different roles – a spectator, judge, the other time a patient or even a therapist. In my researches I will take the challenge to verify to what extent people watching the mentioned shows consider them as needed production – in an educational perpective. I create the list of the reasons to watching those shows, based on the statements of people I study. I show that young people do not know what to do with their spare time, and are either unable to find appropriate authority in the surrounding world or are aware of people who set a good example but choose the ‘easy life’, life with no values.
Reality show programmes – educational perspective